Performance Comparison of Particle Swarm Optimization and Gravitational Search Algorithm to the Designed of Controller for Nonlinear System - Md Rozali, Sahazati; Rahmat, Mohd Fua'ad; Husain, Abdul Rashid (Hindawi Publishing Corporation, 2014)
This paper presents backstepping controller design for tracking purpose of nonlinear system. Since the performance of the designed controller depends on the value of control parameters, gravitational search algorithm (GSA) and particle swarm optimization(PSO) techniques are used to optimise these parameters in order to achieve a predefined system performance. The performance is evaluated based on the tracking error between reference input given to the system and the system output. Then, the efficacy of the backstepping controller is verified in simulation environment under various system setup including both the system subjected to external disturbance and without disturbance.The simulation results show that backstepping with particle swarm optimization performs better than the similar controller with gravitational search algorithm technique in terms of output response and tracking error.